2013
DOI: 10.11621/npj.2013.0217
|View full text |Cite
|
Sign up to set email alerts
|

Mental age of a child as a basis for elaborating parental competence development strategies

Abstract: Психологический возраст ребенка как основание для проектирования стратегий развития родительской компетентности

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A bibliometric analysis of published works with a search for "parental competence", as shown in the Russian citation index (2008 to 2017), revealed that 0.001% of the total number of studies found there were similar in nature. Brief analysis of some of them allowed us to see the following semantic contexts in the study of pa-rental competence: stage in the development of the adult's personality and the family's resources, as a component of the relationship between parents and children; and characteristics of the relationship between parents and children, considering the children's psychological age and stage in age-related psychological development (Gorlova, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A bibliometric analysis of published works with a search for "parental competence", as shown in the Russian citation index (2008 to 2017), revealed that 0.001% of the total number of studies found there were similar in nature. Brief analysis of some of them allowed us to see the following semantic contexts in the study of pa-rental competence: stage in the development of the adult's personality and the family's resources, as a component of the relationship between parents and children; and characteristics of the relationship between parents and children, considering the children's psychological age and stage in age-related psychological development (Gorlova, 2013).…”
Section: Discussionmentioning
confidence: 99%